Sodobne perspektive družbe: Umetna inteligenca na stičišču znanosti - Bregant, Janez; Aberšek, Boris; Borstner, Bojan (2022)
Contemporary Perspectives of Society: Artificial Intelligence at the Intersection of Sciences. Questions concerning the future of our society are largely related to the development of artificial intelligence (AI). In this publication, AI means the open field of research where social, natural and technical sciences meet. It addresses maybe the currently greatest concern: pros and cons of the rapid AI's evolution in terms of its effects on morality, psychology and education. It contains fourteen articles divided into two parts, the first referring to the intersection of AI, philosophy and ethics, and the second referring to the intersection of AI, psychology and education. Such an interdisciplinary nature of the publication represents its additional value. Namely, the use of each disciplines’ own research methodology contributes to the enhancement of the articles in the sense of AI’s effect on morality, transparency and applicability. Moreover, dealing with the research problems in the introduced way gives way to divers, rich and inventive contributions that while offering solutions often step out of the established box.
Keywords: artificial intelligence; moral responsibility; transparency; education; singularity